(untitled) (International Journal on Stereo & Immersive Media, 2025)
Dynamic hyperstereoscopy is an experimental stereoscopic technique that continuously adjusts interaxial disparity to generate a shifting perception of spatial depth. Instead of imitating visual stability, it presents space as a temporal and embodied phenomenon shaped by the viewer’s adaptive engagement. The research investigates mountainous environments whose complex spatial structures surpass the integrative limits of natural stereopsis. The footage was captured using two drones. The analysis of the qualitative responses indicated a recurring sequence: initial disorientation, followed by perceptual adaptation and improved spatial attunement. The approach is grounded in enactive and embodied perception theory, and is characterised by its aesthetic and investigative nature. The film resonates with the aesthetic principles of slow cinema, a genre that prioritises duration and sensory immersion over narrative clarity. A forthcoming film is set to extend the project into an immersive context, treating spatial ambiguity as an experiential medium and inviting viewers to perceive depth as a dynamic, cognitive process rather than a fixed visual illusion.